2007
DOI: 10.1111/j.1365-2796.2007.01810.x
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine‐lowering therapy does not affect inflammatory markers of atherosclerosis in patients with stable coronary artery disease

Abstract: . Objectives.  A high level of total homocysteine (tHcy) is a risk marker for cardiovascular disease (CVD), and is related to inflammation. We wanted to test the effect of homocysteine‐lowering B‐vitamin therapy, as used in the Western Norway B‐vitamin Intervention Trial (WENBIT), on inflammatory markers associated with atherosclerosis. Design.  Single centre, prospective double‐blind clinical interventional study, randomised in a 2 × 2 factorial design. Subjects and methods.  Ninety patients (21 female) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 42 publications
5
50
0
1
Order By: Relevance
“…Intervention studies carried out evaluating the effect of B vitamins on CRP concentrations have been conducted in subjects who were undergoing haemodialysis [53], or stable coronary artery disease patients [54], or those with hyperhomocysteinemia [55]. Two out of three reported no significant treatment effect on CRP levels [54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention studies carried out evaluating the effect of B vitamins on CRP concentrations have been conducted in subjects who were undergoing haemodialysis [53], or stable coronary artery disease patients [54], or those with hyperhomocysteinemia [55]. Two out of three reported no significant treatment effect on CRP levels [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies carried out evaluating the effect of B vitamins on CRP concentrations have been conducted in subjects who were undergoing haemodialysis [53], or stable coronary artery disease patients [54], or those with hyperhomocysteinemia [55]. Two out of three reported no significant treatment effect on CRP levels [54,55]. However, Chang et al demonstrated that a 3-month intervention with a combined B vitamin supplement effectively lowered tHcy and CRP concentrations in haemodialysis subjects, although this study was a randomised, open-labelled study which used doses higher than those in this current study (folic acid (5 mg/d) and vitamin B complex) [53].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in patients with cardiovascular, neurodegenerative and autoimmune disorders, rather close associations have been described between the concentrations of total homocysteine and immune activation and inflammation markers: for example, neopterin (7,8) and C-reactive protein (9), which themselves are significant predictors of cardiovascular risk (10)(11)(12). Neopterin concentrations serve as a reliable immune response marker because a great amount of neopterin is released by monocyte-derived macrophages and dendritic cells upon stimulation with Th1-type cytokine interferon-γ (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…However, these results have largely been refuted by the predominantly negative results of subsequent trials, including the NORVIT, WENBIT, HOPE-2, VISP, VITATOPS, and VITRO studies (48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). These studies generally had a mean follow-up time of several years and assessed a wide variety of vascular indicators and endpoints including carotid intima-media thickness and flow-mediated dilation (52), markers of arterial inflammation (49)(50)(51)(52)(53)(54)(55)(56)(57)(58), need for revascularization procedures (54), occurrence of thromboembolism (53,55), occurrence of stroke and myocardial infarction (48,50,54,56,57,59), as well as overall or coronary/vascular-related mortality (48,50,51,54,56,59). Unfortunately, there appears to be no effect of homocysteine-lowering Bvitamin therapy on Alzheimer's disease and cognitive decline (66)(67)(68) or type 2 diabetes (69), and the results are conflicting regarding potential effects on bone mineral density and turnover, and fracture occurrence <...>…”
Section: Intervention Studies To Reduce Elevations In Homocysteine Comentioning
confidence: 93%